(untitled) (Research, Society and Development, 2022)
Introduction: Periodontal disease is an infection induced by bacteria. Its behavior depends on factor such as the degree of inflammatoy and immune response of the patient. Primary Health Care (PHC) must resolve the populations health problems at the same time as it articulates with other levels of complexity. The present study proposes to obtain information about safety of dentists linked to the PHC of Cascavel-PR in the management of periodontal disease Methodology: This is a qualitative, prospective study, based on data collected in a questionnaire applied, during the months of November 2020 to March 2021, to dentists of the PHC in the municipality of Cascavel-PR, dividing them into 2 groups: Family Health Unity (FHU) and Basic Health Unit (BHU). Results: 32 (47,8%) of the 67 dentists participated in the research, 20 (62% are female). Their average time since graduation was 29,67 for BHU professionals and 12,55 for the FHU professionals. It was not possible to identify a significant difference between the groups for the variable “number of graduate degrees”. It was statistically found that the FHU group checks the vital signs of patients more frequently. Diabetes and depression were the two most cited conditions when asked about diseases related to the periodontits. The main difficulty encountered by professionals was the lack of necessary materials. Final considerations: The FHU teams seem to be better structured. It is understood that if they had the necessary materials, they could offer better results in the management of periodontal disease.